Renal dysplasia with the ipsilateral ectopic ureter mimicking abscess of the prostate - Grbić, Dragan; Jeremić, Dimitrije; Vojinov, Saša; Popov, Milan; Marušić, Goran (Vojnosanitetski pregled, 2014)
Introduction. In males the ectopic ureter usualy drains into the prostate (50%). During ureteric developement a thin membrane (Chawalla’s membrane) separates the lumen of the ureter and the urogenital sinus at the point where the ureter joins the urogenital sinus. This membrane ruptures allowing urin to drain from the ureter to the urogenital sinus. The authors reported a case of renal dysplasia associated with ipsilateral uretral ectopia mimicking prostatic  abscess. Case report. A subfebrile (37.3°C), 23-year-old patient, otherwise healthy, presented with persistent ascending perineal pain non-responsive to antibiotics and analgetics. Digitorectal examination (DRE) showed asymmetric prostate with a soft, tender, buldging left lobe suggestive of prostatic abscess. The diagnosis was suspected using transrectal ultrasonography (TRUS), but the picture of the anechoic tubular structure in the left lobe of the prostate with a proximal undefined extraprostatic extension and a caudal intraprostatic blind end was incoclusive for the definitive diagnosis of prostatic abscess. Magnetic resonance imaging (MRI) was ordered and definitive diagnosis of renal dysplasia associated with the ipsilateral ectopic ureter filled with inflamed content mimicking prostatic abscess was made. Transurethral incision/minimal resection of the distal, blindly closed end of left ectopic ureter was done. Endoscopic surgical treatment was sufficient for relief of clinical symptoms. The patient’s recovery was uneventful. Conclusion. To the best of our knowledge, a case of renal dysplasia with the ipsilateral ectopic ureter mimicking prostate abscess has not been reported so far. Cystic pelvic malformations in males may result from too craniall sprouting of the ureteral bud, with delayed absorption and ectopic opening of the distal end of the ureter.
Keywords: abnormalities; kidney diseases; ureteral diseases; prostatitis; abscess; diagnosis; differential; urologic surgical procedures; treatment outcome